Eruption and caries status of first permanent molars in children aged 6-7 years: Status erupsi dan karies gigi molar pertama permanen pada anak usia 6-7 tahun - Adam Malik Hamudeng; Khadijah Meirani A; Afniati Rachmuddin; Andi Sri Permatasari (Makassar Dental Journal, 2026)
The prevalence of caries in children is very high, especially in the first permanent molars. The eruption status is an important milestone in a child's development, but it is also a phase that is vulnerable to the development of caries. This literature review explores the factors that influence the eruption status and caries of the first permanent molars in children aged 6-7 years. The first permanent molars are at high risk of caries due to pro-longed exposure to the oral environment. Factors such as genetics, nutrition, general health, and oral hygiene behaviour play a significant role in the eruption status and caries of the first permanent molars in children aged 6-7 years. It is concluded that a comprehensive preventive approach, including education, nutrition, and dental hygiene habits, is necessary to reduce the prevalence of caries in permanent first molars.